An anthropology of architecture - Buchli, Victor, author.
1 online resource (224 pages)
Keywords: Ever since anthropology has existed as a discipline, anthropologists have thought about architectural forms. This book provides the first overview of how anthropologists have studied architecture and the extraordinarily rich thought and data this has produced.With a focus on domestic space - that intimate context in which anthropologists traditionally work - the book explains how anthropologists think about public and private boundaries, gender, sex and the body, the materiality of architectural forms and materials, building technologies and architectural representations. Each chapter uses a broad range of case studies from around the world to examine from within anthropology what architecture 'does' - how it makes people and shapes, sustains and unravels social relations.An Anthropology of Architecture is key reading for students of anthropology, material culture, geography, sociology, architectural theory, design and city planning.